Dos testigos leoneses de la Passio Sancti Pelagii - Suárez González, Ana (Estudios humanísticos. Geografía, historia y arte, 2001)
The Passio Sancti Pelagii is an important hagiographique spanish piece from the X century. We present the fragmentary text of the Passio transmitted in the XII and XIII centuries by two manuscripts of León city in order that such codexes be able to take into consideration by latter studies and editions of this written work.